2010
DOI: 10.2522/ptj.20090167
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Activation and Perceived Loading During Rehabilitation Exercises: Comparison of Dumbbells and Elastic Resistance

Abstract: Comparably high levels of muscle activation were obtained during resistance exercises with dumbbells and elastic tubing, indicating that therapists can choose either type in clinical practice. The Borg CR10 can be a useful aid in estimating intensity of individual rehabilitation protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
158
1
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(172 citation statements)
references
References 34 publications
6
158
1
7
Order By: Relevance
“…The results of this study differ from the results of the study done by Andersen et al (2010) who reported that comparable high levels of muscle activation were obtained during resistance exercises with dumbbells and elastic tubing. In the present study the EMG activity was checked during the maximal resistance given by the DeLorme weights, but the EMG activity decreased in the TSLR group.…”
Section: Resultscontrasting
confidence: 57%
“…The results of this study differ from the results of the study done by Andersen et al (2010) who reported that comparable high levels of muscle activation were obtained during resistance exercises with dumbbells and elastic tubing. In the present study the EMG activity was checked during the maximal resistance given by the DeLorme weights, but the EMG activity decreased in the TSLR group.…”
Section: Resultscontrasting
confidence: 57%
“…This has highlighted the need to examine effects and safety of alternate exercise equipment [3]. Elastic resistance equipment such as elastic bands and tubing offers an alternative that has shown comparable results to weight machines regarding both upper and lower extremity exercises in healthy adults [5,6]. In people with COPD, O´Shea et al [7] found that a predominantly home-based resistance training regimen with elastic bands could be used to increase knee extensor strength.…”
Section: Introductionmentioning
confidence: 99%
“…In laboratory settings, perceived physical exertion relates closely to work demands expressed as a percentage of the individual physical capacity -both in terms Andersen et al of cardiovascular (12) and muscular work loadings (13). Thus, to some extent, perceived physical exertion reflects the balance between physical work demands and physical capacity of the individual.…”
mentioning
confidence: 99%